2007
DOI: 10.1016/j.bbamem.2007.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Action mechanism of tachyplesin I and effects of PEGylation

Abstract: PEGylation of protein and peptide drugs is frequently used to improve in vivo efficacy. We investigated the action mechanism of tachyplesin I, a membrane-acting cyclic antimicrobial peptide from Tachypleus tridentatus and the effects of PEGylation on the mechanism. The PEGylated peptide induced the leakage of calcein from egg yolk L-alpha-phosphatidylglycerol/egg yolk L-alpha-phosphatidylcholine large unilamellar vesicles similarly to the parent peptide. Both peptides induced lipid flip-flop coupled to leakage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
138
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(151 citation statements)
references
References 55 publications
13
138
0
Order By: Relevance
“…Thus, modification of MG 2 with PEG (5 kDa) resulted only in slightly reduced antimicrobial activity and did not change the interaction patterns with lipid bilayers [155]. Similar observations were made with β-sheet tachyplesin [156]. In contrast, the loss of the antimicrobial activity of PEG-nisin [144] could only be explained by the disturbance of the peculiar mechanism of action, which is based on selective lipid II binding and consecutive migration of the peptide's C terminus through the cell membrane.…”
Section: Antimicrobial Activity Of the Free Peptidessupporting
confidence: 69%
See 1 more Smart Citation
“…Thus, modification of MG 2 with PEG (5 kDa) resulted only in slightly reduced antimicrobial activity and did not change the interaction patterns with lipid bilayers [155]. Similar observations were made with β-sheet tachyplesin [156]. In contrast, the loss of the antimicrobial activity of PEG-nisin [144] could only be explained by the disturbance of the peculiar mechanism of action, which is based on selective lipid II binding and consecutive migration of the peptide's C terminus through the cell membrane.…”
Section: Antimicrobial Activity Of the Free Peptidessupporting
confidence: 69%
“…One might speculate that these small changes are due to the low molecular weight of the attached PEG 2 moiety. However, recently it has been reported that even coupling of much larger PEG units did not influence the basic mechanism of membrane permeabilization of amphipathic peptides [155,156]. Thus, modification of MG 2 with PEG (5 kDa) resulted only in slightly reduced antimicrobial activity and did not change the interaction patterns with lipid bilayers [155].…”
Section: Antimicrobial Activity Of the Free Peptidesmentioning
confidence: 96%
“…Furthermore, PEGylated proteins/peptides frequently display increased resistance to proteolytic degradation, as well as reduced aggregation, toxicity, and immune responses. Also for AMPs, PEGylation may result in reduced proteolytic susceptibility and toxicity, but generally at a cost of reduced antimicrobial effect (42,43 antimicrobial potency in an Mw-dependent manner, but also in a strongly reduced toxicity and in improved selectivity. After PEGylation, conditions could be found, at which the PEGylated peptide was able to effectively kill bacteria added to blood, but at the same time causing no measurable hemolysis.…”
Section: Pegylation For Enhanced Amp Performancementioning
confidence: 99%
“…Previous studies showed that tachyplesin I can kill bacteria by permeabilizing the bacterial membrane and acting on intracellular targets in bacteria to inhibit DNA, RNA, and protein synthesis and enzyme activity (11)(12)(13). Tachyplesin I acts similarly to magainin-2, MSI-78, and LL-37 by forming a toroidal transmembrane pore (14). Thus, tachyplesin I exhibits multiple effects and synergistic antibacterial mechanisms, and the development of X33-GAP-TPI yeast strains that express recombinant tachyplesin I at high levels has facilitated its use as a novel alternative antibiotic for wide use in pharmaceuticals and animal feed in the future (15,16).…”
mentioning
confidence: 99%